The antiviral activity of poly-γ-glutamic acid, a polypeptide secreted by Bacillus sp., through induction of CD14-dependent type I interferon responses - Lee, Wooseong (Biomaterials, 2013)
Poly-γ-glutamic acid (γ-PGA) is an anionic polypeptide secreted by Bacillus sp. that has been shown to activate immune cells through interactions with toll-like receptor 4 (TLR4). However, its ability to induce the type I interferon (IFN) response has not yet been characterized. Here, we demonstrate that γ-PGA induces type I IFN signaling pathway via the TLR4 signaling pathway. The induction required both myeloid differentiation factor 2 (MD2) and the pattern-recognition receptor CD14, which are two TLR4-associated accessory proteins. The γ-PGA with high molecular weights (2000 and 5000 kDa) was able to activate the subsequent signals through TLR4/MD2 to result in dimerization of IRF-3, a transcription factor required for IFN gene expression, leading to increases in mRNA levels of the type I IFN-response genes, 2′–5′ OAS and ISG56. Moreover, γ-PGA (2000 kDa) displayed an antiviral activity against SARS coronavirus and hepatitis C virus. Our results identify high-molecular weight γ-PGA as a TLR4 ligand and demonstrate that γ-PGA requires both CD14 and MD2 for the activation of type I IFN responses. Our results suggest that the microbial biopolymer γ-PGA may have therapeutic potential against a broad range of viruses sensitive to type I IFNs.